The singularity of the medicinal knowledge of the Huni Kuĩ people from the western Brazilian Amazon - Penedo, Thiago Serrano de Almeida Penedo; Quinet, Alexandre; Haverroth, Moacir; Luna Peixoto, Ariane (Ethnobotany Research and Applications, 2023)
Background: Studies that aim to analyze the transcultural traditional knowledge from different countries still in their infancy but are essential to favor an equal and fair division of the benefits resulting from the exploration of genetic resources and to develop sustainable strategies for conservation. The goal of this research is to compare the traditional knowledge about medicinal plants by the Huni Kuĩ people with the knowledge from other cultures, in order to assess the singularity of the Huni Kuĩ knowledge and to identify the convergence in medicinal plants use with other cultures. Methods: We did a literature review for 83 plant species and compiled all traditional knowledge available on the Scielo PubMed and Google Scholar. We searched for the scientific name of each species and its synonyms (382) plus the words “ethnobotany”, “ethnobotanical” or “medicinal” as inclusion criteria. Results: We found 625 papers for 54 plants. About 73% of the medicinal services found for these species were considered, and 90% of all medicinal services cited were from the Huni Kuĩ people. The other 10% (20 species) were shared with other communities. Most of the research was conducted in the Brazilian Amazon, but also in the other countries. Conclusion: Our results show the singularity of the Huni Kuĩ knowledge and the complexity in the distribution of traditional knowledge, which highlights the importance of projects that document the traditional knowledge, in order to create new conservation strategies and public policies. Keywords: traditional knowledge, indigenous people, indigenous language, medicinal services, ethnobotany